THE CONVERSION OF N – METHYLANILINE AND N –, 2 – DIMETHYLANILINE BY USING DIFFERENT CATALYSTS - Akbar Ali, Aghayev; Abdulla, Musfatayeva Naila; Turabkhan, Shahtakhtinskaya Pari; Mayil, Muradov Mahal; Mammad, Nasirova Irada (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The catalytic conversion of N methylaniline and N, 2 dimethylaniline in the presence of Pd HSHM, CuFe2O4Â·Î³Â·Al2O3 and vanadium chromium aluminium (VChA) oxide systems has been investigated. The comparative analysis of the results of the conversion of three different feedstocks with VChA catalyst shows that the xylidines, especially 2,6 dimethylaniline is formed as a result of the methylation of aromatic amine because of the carbon in nucleus.